A comparison of two versus four sterile water injections for the relief of back pain in labour: A multicentre randomised equivalence trial. Issue 6 (November 2022) - Lee, Nigel; Leiser, Bernadette; Halter-Wehrli, Yvonne; Mårtensson, Lena B.; Gao, Yu; Kildea, Sue
Abstract: Background: Recent trials demonstrated the safety and efficacy of sterile water injections to provide relief from labour back pain. While four injections is the most common approach variations in technique, such as employing two injections, are also used. Aim: To determine if the analgesic effect of two sterile water injections is clinically equivalent to four. Methods: 238 women in labour with a Visual Analogue Scale pain score (VAS) of 70 millimetres (mm) (0 = no pain; 100 = worst pain imaginable) were randomised to two or four sterile water injections. The primary outcome was pain measured on a VAS at 30 min post treatment. A priori margin of equivalence was set at ±10 mm. Secondary outcomes included the likelihood of achieving an at least 30% and 50% reduction in pain, birth and neonatal outcomes. Results: At 30 min post-injection the difference in VAS scores between the techniques was −5.97 (95% Confidence Interval [CI] −13.18–1.22). As the lower end of the CI exceeds the margin of −10 mm equivalence was not demonstrated. Both techniques achieved an at least 30% reduction in pain in over 75% of participants though duration of effect was longer in the four injection group. There was no difference in other birth related secondary outcomes. Conclusion: Four injections provided a margin of benefit over two injections in level and duration of analgesia. Discussion: Four injections remains the technique of choice though two injections still provided significant pain relief and would be suitable where it was not possible or desirable to provide four.